Effect of Work Environment, Work Discipline, and Work Ethic on Organizational Citizenship Behavior (OCB) (A Study of TVRI Yogyakarta Station Employees) - Rizka Ayu Septiani; Kusuma Chandra Kirana; Tri Ratna Purnamarini (Admisi dan Bisnis, 2026)
This study aims to examine the effect of work environment, work discipline, and work ethic on Organizational Citizenship Behavior, among employees of TVRI Yogyakarta. OCB is the term for volunteer actions that enhance organizational effectiveness. This study used a survey method with a quantitative approach. 70 respondents who were chosen using a saturation sampling technique. The impact of the independent variables on OCB was investigated using multiple linear regression analysis. The findings show that OCB is positively and significantly impacted by the work environment and work discipline, indicating that favorable working conditions and compliance with organizational policies improve employees’ extra-role behavior. In the meanwhile, OCB is positively but marginally impacted by work ethic. These results suggest that enhancing the work environment and bolstering work discipline are crucial tactics for raising OCB. The results may not as broadly applicable as they could be because this study restricted to a specific organization.